Teaching Animals in the Post-Anthropocene: Zoopedagogy as a Challenge to Logocentrism - Anastassiya Andrianova (Journal of the Assembly for Expanded Perspectives on Learning, 2019)
This essay examines a theory and practice of zoopedagogy that encourages exploring non-logocentric mode(l)s of communication while promoting environmentalism, critical thinking, and empathy.